Switchgrass Bale Automatic Weighing and Watering System - Ni Nyoman Sulastri; Shelyn Gehle (Program Studi Teknik Pertanian, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2020)
The purpose of this study was to maintain minimum moisture content for switchgrass bales that were inoculated with Pleurotus ostreatus, a white-rot fungus, in order to start the breakdown of lignin for conversion to ethanol. The moisture content was to be maintained above 50%, which would be monitored using load cells to determine the weight. Three bales were used, and thermocouple wires and hose system were placed at four points inside each bale. In addition, the ambient temperature and relative humidity inside the building were monitored. Bales were inoculated with 1%, 2%, and 3% grain spawn by mass. The inoculation was carried out by taking the bale apart in four places and sprinkling or spreading the fungal spawn over the bale. In order to continuously record the voltage readings from the strain gauges, NI USB-6225 data logger and National Instruments’ LabVIEW program was used to record and control the system. The develop automatic weighing and watering system had been able to maintain the bale moisture within the acceptable range and the fungus were observed growing. Some issues related to voltage readings and uniformity of water distribution must be addressed for future work.